2015
DOI: 10.1080/1351847x.2015.1048375
|View full text |Cite
|
Sign up to set email alerts
|

Stock market investors' use of stop losses and the disposition effect

Abstract: The disposition effect is an investment bias where investors hold stocks at a loss longer than stocks at a gain. This bias is associated with poorer investment performance and exhibited to a greater extent by investors with less experience and less sophistication. A method of managing susceptibility to the bias is through use of stop losses. Using the trading records of UK stock market individual investors from 2006 -2009, this paper shows that stop losses used as part of investment decisions are an effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 49 publications
(93 reference statements)
0
18
0
1
Order By: Relevance
“…On the contrary to that Talpsepp (2013) provides evidence that the portfolios of female investors perform better than the portfolios of male investors. Richards et al, (2017) find evidence that men are more likely to hold losses longer because of that they are more willing to the disposition effect than women. Singh & Bhattacharjee (2010a) found that gender has a significant role to play in equity investing.…”
Section: Tax-loss Selling (Tls)mentioning
confidence: 84%
See 3 more Smart Citations
“…On the contrary to that Talpsepp (2013) provides evidence that the portfolios of female investors perform better than the portfolios of male investors. Richards et al, (2017) find evidence that men are more likely to hold losses longer because of that they are more willing to the disposition effect than women. Singh & Bhattacharjee (2010a) found that gender has a significant role to play in equity investing.…”
Section: Tax-loss Selling (Tls)mentioning
confidence: 84%
“…Investor's sophistication (IS): Sophisticated investors are less resistant to realize a loss (Brown et al, 2006;Richards, Rutterford, Kodwani & Fenton-O'Creevy, 2017;Choe & Eom, 2006;Leal, Armada & Duque, 2008). Empirical evidence suggests that professional traders who trade on behalf of others are less susceptible to causing disposition effects (Shapira & Venezia, 2001;Dhar & Zhu, 2006).…”
Section: Trading Intensity (Ti)mentioning
confidence: 99%
See 2 more Smart Citations
“…También en el ámbito de los mercados financieros, Ranguelova (2001) observa que el efecto disposición se concentra principalmente en acciones de gran capitalización, mientras las acciones situadas en el 40% inferior de la distribución según tamaño, muestran un efecto disposición inverso Kaustia (2010): los inversores mantienen sus ganancias y realizan sus pérdidas, poniendo así en duda que la aversión a las pérdidas sea una posible explicación del efecto disposición. Recientemente, Richards et al (2017) argumentan que una forma relativamente sencilla de reducir el efecto disposición en el mercado de valores es mediante el uso de órdenes stop loss, ya que éstos pueden automatizar una salida estratégica reduciendo el impulso del inversor. Además, Nolte (2012) (2005) en China.…”
Section: Introductionunclassified